Contribuição ao estudo da utilização de materiais de mudança de fase em sistemas de arrefecimento de componentes eletrônicos - Ferreira, Antonio Carlos (1993)
Recently the literature has been showing computational codes that are able to model the behaviour of phase change materiais when submitted to various configurations and processes of heat transfer, mainly in processes of its melting and freezing. The present work is a contribution to the development of such codes particularly filling some gaps of those configurations. Using the technique of finite control volume, of Patankar, the equations of energy and of momentum, in the bidimensional form coupled through the hypothesis of Boussinesq for the inclusion of the effect of natural convection under melted phase, were numerically solved. O effect of latent heat was simulated through well tested model of Bonacina. The studied geometry was flat, infinite and submitted in a face to a heat flux dissipated by an electronic component, and in a others faces the heat losses were by convection. Results are presented for various geometrical parameters and heat transfer, through the fusion fronts, the fraction of melted mass, the stored heat and the field of temperatures on the surface of the phase change material, in contact with the eletronic component.